Effect of Varying Thiophene Units on Charge‐Transport and Photovoltaic Properties of Poly(phenylene ethynylene)‐alt‐poly(phenylene vinylene) Polymers. Issue 15 (18th June 2014) - Adam, Getachew; Yohannes, Teketel; White, Matthew; Montaigne, Alberto; Ulbricht, Christoph; Birckner, Eckhard; Rathgeber, Silke; Kästner, Christian; Hoppe, Harald; Sariciftci, Niyazi Serdar; Egbe, Daniel Ayuk Mbi
<x xml:space="preserve">Abstract</x> Poly(phenylene ethynylene)‐alt‐poly(phenylene vinylene)s (PPE‐PPVs) with various thiophene units (thiophene, bithiophene, and 3, 4‐ethylenedioxythiophene) at the X position, with the general backbone design (PhCCXCCPhCHCHPhCHCH), bearing identical solubilizing side chains at the phenylene rings of the polymers, are synthesized to study the effect of this structural alteration on the properties such as the photophysics, the electrochemical properties, the charge‐carrier mobility, and the morphology of the materials and its impact on their photovoltaic performance. The polymers are obtained in good yields with reasonable molecular weights and show solubility in ordinary organic solvents required for solution‐processing applications. The polymer with a basic thiophene ring at the X positions shows the highest open‐circuit voltage (VOC of 930 mV) and the polymer with a bithiophene unit at the X position shows the highest short‐circuit current density and charge‐carrier mobility, whereas the polymer with 3, 4‐ethylenedioxythiophene shows the lowest photovoltaic performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>